2021
DOI: 10.1007/s10096-021-04153-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for respiratory tract bacterial colonization and infection in lung transplant recipients

Abstract: To evaluate incidence of and risk factors for respiratory bacterial colonization and infections within 30 days from lung transplantation (LT). We retrospectively analyzed microbiological and clinical data from 94 patients transplanted for indications other than cystic fibrosis, focusing on the occurrence of bacterial respiratory colonization or infection during 1 month of follow-up after LT. Thirty-three percent of patients developed lower respiratory bacterial colonization. Bilateral LT and chronic heart dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…It showed that LVR was associated with a distinct airway microbiome both before and after LuTX. In comparison to other LuTX-indications COPD has a lower risk of bacterial infections ( 25 ). It was unexpected that the number of colonized patients were as high even before LuTX (LVRS: 42.3%; ELVR: 39.3%).…”
Section: Discussionmentioning
confidence: 99%
“…It showed that LVR was associated with a distinct airway microbiome both before and after LuTX. In comparison to other LuTX-indications COPD has a lower risk of bacterial infections ( 25 ). It was unexpected that the number of colonized patients were as high even before LuTX (LVRS: 42.3%; ELVR: 39.3%).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the present study is the first investigation exclusively focused on bilateral LT recipients, without restrictions on previous colonization and considering a wide spectrum of culture samples. 2,4,11,21 These assumptions allowed us to investigate the overall incidence of MDR and ESBL GN bacteria and to study the effect of broad-spectrum antibiotics administered empirically in a homogeneous cohort of recipients, investigations that were not comparable with previous studies also enrolling patients undergoing monolateral LT. 10,13,15,16,25 Based on recent literature, the incidence of MDR after LT is unclear. Paglicci et al 21 retrospectively investigated a cohort of 94 LT procedures from 2001 through 2018 and reported a slightly lower incidence than ours (31%), but patients affected by cystic fibrosis had been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,11,21 These assumptions allowed us to investigate the overall incidence of MDR and ESBL GN bacteria and to study the effect of broad-spectrum antibiotics administered empirically in a homogeneous cohort of recipients, investigations that were not comparable with previous studies also enrolling patients undergoing monolateral LT. 10,13,15,16,25 Based on recent literature, the incidence of MDR after LT is unclear. Paglicci et al 21 retrospectively investigated a cohort of 94 LT procedures from 2001 through 2018 and reported a slightly lower incidence than ours (31%), but patients affected by cystic fibrosis had been excluded. However, Tebano et al 4 reported a higher overall MDR incidence than ours (51%), but gram-positive bacteria and more than 70% of monolateral LT recipients were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study has shown that the BMI of organ recipients is a risk factor for surgical incision infection after lung transplantation, and the BMI of patients with infection is significantly higher than those without (21). The median BMI of lung transplant patients with surgical incision site infection was greater than 24 kg/m 2 (22).…”
Section: Body Mass Index (Bmi) Of the Organ Recipientmentioning
confidence: 98%